Effect Aerobic Exercises on fatigue and quality of life in Women with Multiple Sclerosis - Bayan Fayazi; Abdolhossein Parnow; Behrooz Ahsan (Guilan University of Medical Sciences, 2016)
Introduction: Multiple Sclerosis Multiple Sclerosis is a chronic and autoimmune disease. Muscle weakness and fatigue leads to decreased functional capacities and diminished quality of life in Multiple Sclerosis patients Objective: The purpose of this study was to determine the effect of aerobic exercises on fatigue and quality of life in women with Multiple Sclerosis Methods: Fifteen women with Multiple Sclerosis (aged 33.68±8.22 years) and Expanded Disability StatusScale < 4 participated in this study. Subjects were randomly divided to experimental (8 patients) and control group (7 patients). The experiment group went through Modified Fatigue Impact Scale-5 aerobic activity for 8 weeks, 3 days/week, 20-40 min/day, with 60-80% of maximum Heart Rate on treadmill. Modified Fatigue Impact Scale-5 questionnaire on fatigue and quality of life (SF-36) and additionally, walking endurance of subjects were measured before and after program in both experimental and control groups Results: Data analysis showed that the aerobic exercise led to improvement of quality of life in MS patients (P=0.001). Therefore, the exercise program led to a significant decrease in fatigue in experimental group (P=0.001); while fatigue increased in control group. Additionally, after the 8-week aerobic activity, walking endurance increased significantly in experimental group (P=0.000); and decreased significantly in control group (P=0.04). Conclusion: Considering study results, it can be stated that aerobic exercises may increase walking endurance and improvement of quality of life of Multiple Sclerosis patients and decrease fatigue